HO‐1 in lymph node metastasis predicted overall survival in patients with esophageal squamous cell carcinoma receiving neoadjuvant chemoradiation therapy. Issue 3 (15th July 2021) - Akaishi, Ryujiro; Fujishima, Fumiyoshi; Ishida, Hirotaka; Tsunokake, Junichi; Yamauchi, Takuro; Gokon, Yusuke; Ueki, Shunsuke; Fukutomi, Toshiaki; Okamoto, Hiroshi; Takaya, Kai; Sato, Chiaki; Taniyama, Yusuke; et al.
Abstract: Background: Lymph node metastasis is one of the pivotal factors of the clinical outcomes of patients with esophageal cancer receiving neoadjuvant chemoradiation therapy (NACRT). Both the nuclear factor‐erythroid 2‐related factor 2 (Nrf2) signaling pathway and heme oxygenase‐1 (HO‐1) are frequently upregulated in various human malignancies and associated with resistance to chemoradiation therapy, subsequently resulting in adverse clinical outcomes. However, the Nrf2 and HO‐1 status in lymph node metastasis and their differences between primary and metastatic lesions are unknown. Aims: To examine the levels of Nrf2 signaling proteins and HO‐1 in primary and metastatic lesions of patients with esophageal squamous cell carcinoma using immunohistochemistry. Methods and Results: We immunolocalized Nrf2 signaling proteins in 69 patients with lymph node metastases, who received NACRT with 5‐fluorouracil and cisplatin before esophagectomy. We also compared the findings between primary and metastatic lesions. Residual lymph node metastases were detected in 30 patients and among them, both primary and metastatic lesions were available for evaluation in 25 patients. Subsequently, we correlated the results with patients' survival. Nrf2, HO‐1, and the Ki‐67 labeling index were all significantly lower in the patients with lymph node metastases than in those with primary tumors. Carcinoma cells with high HO‐1 levels were significantly associated with pathological resistance to NACRT. These results suggested that overall and disease‐free survival of esophageal squamous cell carcinoma were significantly associated with both pN2 and high HO‐1 levels, respectively. Conclusions: Protein expression in the Nrf2 pathway was significantly lower in patients with lymph node metastases than in those with primary lesions. HO‐1 levels in lymph node metastases could be used to predict the eventual clinical outcome of patients with esophageal cancer receiving NACRT.